Bridging the gap: Teachers' grasp and execution of technology-enhanced flipped classrooms - Ishak, Mohd Faisal Farish bin; Sa’don, Nor Fadzleen binti; Abdullah, Yasmine Leong Pui Kwan binti (CV. Yudhistt Fateeh, 2024)
This article presents an assessment of the implementation of flipped classrooms and the use of Edpuzzle for this purpose. Four elementary schools engaging in the School Transformation Programme 2025 (TS25) across various subject areas were included in the study. As part of this programme, teachers received training in pedagogical and technological knowledge. A mixed-methods design was employed to collect and analyse both quantitative and qualitative data. The findings indicate that teachers demonstrated a strong understanding of the pupil-centred concept in the flipped classroom model. However, while teachers universally used Edpuzzle for pre-class activities, there is a need for them to fully leverage its features and enhance creativity to develop more engaging video quizzes.